Dose‐dependent exposure profile and metabolic characterization of notoginsenoside R1 in rat plasma by ultra‐fast liquid chromatography–electrospray ionization–tandem mass spectrometry. (28th August 2019) - Zhang, Sainan; Ju, Zhengcai; Guan, Huida; Yu, Lu; Wang, Zhengtao; Zhao, Yuqing
Abstract: Notoginsenoside R1 (NGR1 ), a diagnostic protopanaxatriol‐type (ppt‐type) saponin in Panax notoginseng, possesses potent biological activities including antithrombotic, anti‐inflammatory, neuron protection and improvement of microcirculation, yet its pharmacokinetics and metabolic characterization as an individual compound remain unclear. The aim of this study was to investigate the exposure profile of NGR1 in rats after oral and intravenous administration and to explore the metabolic characterization of NGR1 . A simple and sensitive ultra‐fast liquid chromatographic–tandem mass spectrometric method was developed and validated for the quantitative determination of NGR1 and its major metabolites, and for characterization of its metabolic profile in rat plasma. The blood samples were precipitated with methanol, quantified in a negative multiple reaction monitoring mode and analyzed within 6.0 min. Validation parameters (linearity, precision and accuracy, recovery and matrix effect, stability) were within acceptable ranges. After oral administration, NGR1 exhibited dose‐independent exposure behaviors with t 1/2 over 8.0 h and oral bioavailability of 0.25–0.29%. A total of seven metabolites were characterized, including two pairs of epimers, 20( R )‐notoginsenoside R2 /20( S )‐notoginsenoside R2 and 20( R )‐ginsenoside Rh1 /20( S )‐ginsenoside Rh1, with the 20( R ) form of saponins identified for the first time in rat plasma. Five deglycometabolites were quantitatively determined, among which 20( S )‐notoginsenoside R2, ginsenoside Rg1, ginsenoside F1 and protopanaxatriol displayed relatively high exploration, which may partly explain the pharmacodynamic diversity of ginsenosides after oral dose.